2023
DOI: 10.3390/vaccines11020300
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Provider’s Perceived Self-Efficacy in HPV Vaccination Hesitancy Counseling and HPV Vaccination Acceptance

Abstract: Background: HPV vaccine hesitancy is a key contributor to the sub-optimal HPV vaccination uptake in the United States. We aimed to determine the association between healthcare providers’ self-efficacy in HPV vaccination hesitancy counseling and HPV vaccination acceptance after initial and follow-up counseling sessions. Methods: Population-based cross-sectional study of healthcare providers (HCPs) practicing in Texas. Logistic regression analyses were used to determine the odds of HPV vaccination acceptance by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…A community-based intervention in the United States addressed the knowledge and confidence gap regarding COVID-19 vaccination by employing branching logic and customizing content based on the user's geographical location, rural-urban classification, race/ethnicity, and access to child-age-specific information [30]. Additionally, Osaghae's research has demonstrated that parents exhibiting vaccine hesitancy were 61% more inclined to consistently receive HPV vaccination following follow-up counseling than their initial counseling session, further substantiating the significance of post-counseling interventions [31]. This suggests that during the training of HCWs in community health service centers, emphasis should be placed on cultivating the awareness of HCWs to provide consulting services and the flexibility of consultation proactively.…”
Section: Consulting Preferences Between Hcws and Residentsmentioning
confidence: 92%
“…A community-based intervention in the United States addressed the knowledge and confidence gap regarding COVID-19 vaccination by employing branching logic and customizing content based on the user's geographical location, rural-urban classification, race/ethnicity, and access to child-age-specific information [30]. Additionally, Osaghae's research has demonstrated that parents exhibiting vaccine hesitancy were 61% more inclined to consistently receive HPV vaccination following follow-up counseling than their initial counseling session, further substantiating the significance of post-counseling interventions [31]. This suggests that during the training of HCWs in community health service centers, emphasis should be placed on cultivating the awareness of HCWs to provide consulting services and the flexibility of consultation proactively.…”
Section: Consulting Preferences Between Hcws and Residentsmentioning
confidence: 92%
“…Selaras dengan penelitian Zulfa (2021) dan Simajuntak (2023), bahwa dengan memberikan pengetahuan mengenai kanker serviks dapat meningkatkan minat orangtua/ wali pada minat vaksin HPV pada anak dan didapatkan adanya sikap positif dalam penerimaan vaksinasi HPV (Simanjuntak & Sugiharto, 2023;Zulfa et al, 2021). Sedangkan penelitian Strbac (2023) dan Osaghae (2023), didapatkan adanya pengaruh terhadap sikap positif ibu mengenai vaksinasi HPV dengan memberikan konseling dan edukasi serta rekomendasi vaksinasi HPV (Osaghae et al, 2023;Štrbac et al, 2023).…”
Section: Issn: 2808-6988unclassified